A compact and lightweight small animal PET with uniform high-resolution for onboard PET/CT image-guided preclinical radiation oncology research. (19th October 2021) - Cheng, Xinyi; Hu, Kun; Yang, Dongxu; Shao, Yiping
Abstract: Objective: In contrast to clinical radiation therapy (RT) that ubiquitously uses PET/CT image to accurately guide RT, all current commercial animal irradiators can only provide CT image-guided preclinical RT that severely limits their capability for preclinical and compatibility for translational radiation oncology research. To address this problem, we have developed a compact and lightweight PET with uniform, high spatial resolution that is suited to be installed inside an existing animal irradiator for potential onboard PET/CT image-guided preclinical RT research. Approach: The design focused on the balance of achieving sufficient imaging performance for practical preclinical RT guidance with constrained size and weight. The detector head consists of a ring of 12 detector panels in a dodecagon configuration and 12 front-end electronics boards that are closely attached to the detector panels. The overall size and weight of the detector head are 33.0 cm diameter, 11.0 cm axial length and ∼6.5 kg weight that can be installed inside an existing irradiator. Each detector panel has a 30 × 30 array of 1 × 1 × 20 mm 3 LYSO scintillators with depth-of-interaction (DOI) measurement. The front-end electronics boards process and convert detected signals to digital signals and transfer them to system electronics and data acquisition located outside the irradiator through low-voltage-differential-signaling cables. Main results: The typical energy, DOI and coincidence timing resolutions are around 22.1%, 3.1 mm, and 1.92 ns. The imaging field-of-view (FOV) is 8.0 cm diameter and 3.5 cm axial length. The performance evaluations show a 1.8% sensitivity at the center FOV, uniform ∼1.1 mm resolution within 6 cm diameter FOV, and all rods of 1.0 mm diameter can be clearly resolved from the image of an ultra-micro hot-rods phantom. Significance: Overall, this compact and lightweight PET has demonstrated its designed capability and performance sufficient for providing onboard functional/biological/molecular image to guide the preclinical RT research.